2018
DOI: 10.1002/jia2.25186
|View full text |Cite
|
Sign up to set email alerts
|

Sexually transmitted infections and HIV RNA levels in blood and anogenital compartments among Thai men who have sex with men before and after antiretroviral therapy: implication for Treatment as Prevention programme

Abstract: IntroductionSexually transmitted infections (STIs) are common among HIV‐positive men who have sex with men (MSM). There have been concerns that undiagnosed and untreated STIs could undermine efforts to use antiretroviral therapy (ART) for prevention due to genital secretion infectiousness. We evaluated the correlation between STIs and HIV RNA in anogenital compartments among HIV‐positive MSM before and after ART.MethodsMSM participants newly diagnosed with HIV were offered ART regardless of CD4 count during No… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 26 publications
0
6
0
Order By: Relevance
“…In our study, about three-quarters of HIV-infected men with incident syphilis had undetectable viral load at the time they were tested positive for syphilis, and there was no significant difference in the proportion between MSM and heterosexual men (figure 2). While a study found no evidence of STIs altering the paradigm of ‘Undetectable=Untransmittable’ (‘U=U’) among HIV-positive MSM on ART in Thailand, those with STIs had higher levels of anogenital HIV RNA at the time of diagnosis, especially prior to commencement of ART 29. This underscores the importance of integrating asymptomatic STI screening as part of universal treatment as prevention strategies.…”
Section: Discussionmentioning
confidence: 98%
“…In our study, about three-quarters of HIV-infected men with incident syphilis had undetectable viral load at the time they were tested positive for syphilis, and there was no significant difference in the proportion between MSM and heterosexual men (figure 2). While a study found no evidence of STIs altering the paradigm of ‘Undetectable=Untransmittable’ (‘U=U’) among HIV-positive MSM on ART in Thailand, those with STIs had higher levels of anogenital HIV RNA at the time of diagnosis, especially prior to commencement of ART 29. This underscores the importance of integrating asymptomatic STI screening as part of universal treatment as prevention strategies.…”
Section: Discussionmentioning
confidence: 98%
“…The test-and-treat approach combines periodic HIV testing and immediate ART initiation. At-risk populations screened within this intervention strategy are motivated to initiate ART as soon as possible, thereby achieving a life expectancy similar to HIV-uninfected people [22, 36, 37]. In 2012, 810 Thai MSM and TGW were enrolled in a test-and-treat study in Bangkok, Ubon Ratchathani, Lampang and Mahasarakam that newly-diagnosed 134 (16.5%) PLWH [38].…”
Section: Introductionmentioning
confidence: 99%
“…Among gay men on ART in Thailand, ART effectively suppressed HIV RNA at months 12 and 24 after initiating ART although the rates of STIs remained high during the study. 20 STIs do not increase infectiousness of HIV-positive index cases, as demonstrated in HPTN 052 and more recently in studies of MSM. 21,22 Given the potency and effectiveness of ART in reducing viral load and preventing HIV transmission, any relative contribution of STIs to HIV acquisition appears difficult to quantify for those on ART.…”
Section: Discussionmentioning
confidence: 66%